Advantages and disadvantages that teachers face while teaching through Google Classroom Platform at Centro Escolar República de Nicaragua in Quezaltepeque, La Libertad, year 2020. - Monterroza Quijada, Oswaldo Balmore
The advantages and disadvantages that teachers have while switching from face to face classes to Google Classroom Platform is an important issue to study because it is necessary to explore how teachers could deal with this change. Researchers decided to investigate this topic because during the year 2020, all the schools and universities turned to online classes due to Covid-19 Pandemic, which affected all around the world. Schools were closed to keep students and teachers away from this contagious virus. Teachers from Centro Escolar República de Nicaragua were chosen to be the sample since all of them use the Google Classroom Platform to get in contact with students and continue their study program. To reach the objectives in this research, the type of research was the mixed method since both, quantitative and qualitative approaches were used through an online survey where they filled out a questionnaire that described their performance in their classes. Participants were able to help with this research. After exploring their performance, conditions, and structure for their online classes; researchers concluded that teachers had the necessary skills to implement the use of LMS, even though it implied opportunities and obstacles to overcome because they lacked knowledge at the beginning and financial support as well. Notwithstanding, they learned the use of Google Classroom highly well. Key words: Pandemic COVID-19 ; LMS ; Google Classroom Platform ; Face to face classes ; Online class.